2009
DOI: 10.1089/ten.teb.2008.0193
|View full text |Cite
|
Sign up to set email alerts
|

Vascularization—The Conduit to Viable Engineered Tissues

Abstract: Long-term viability of thick three-dimensional engineered tissue constructs is a major challenge. Addressing it requires development of vessel-like network that will allow the survival of the construct in vitro and its integration in vivo owing to improved vascularization after implantation. Resulting from work of various research groups, several approaches were developed aiming engineered tissue vascularization: (1) embodiment of angiogenesis growth factors in the polymeric scaffolds for prolonged release, (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
147
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 284 publications
(154 citation statements)
references
References 86 publications
2
147
0
1
Order By: Relevance
“…In this study, we demonstrated a means of directing tube assembly using tensile forces, as well as the importance of cell orientation in network structuring. Although other studies have focused on guiding cell orientation using specific patterns or by growing ECs without stromal cell support (11,42,43), here, we relied on self-assembly of a coculture of fibroblasts and ECs and observed formation of a stable and mature vascular network, affected only by the applied tensile forces (24,44). Both static and cyclic forces were examined because they were shown to have differential effects on ECs grown in 2D settings (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we demonstrated a means of directing tube assembly using tensile forces, as well as the importance of cell orientation in network structuring. Although other studies have focused on guiding cell orientation using specific patterns or by growing ECs without stromal cell support (11,42,43), here, we relied on self-assembly of a coculture of fibroblasts and ECs and observed formation of a stable and mature vascular network, affected only by the applied tensile forces (24,44). Both static and cyclic forces were examined because they were shown to have differential effects on ECs grown in 2D settings (45).…”
Section: Discussionmentioning
confidence: 99%
“…Implantation of grafts bearing networks arranged to match those in the implant site is expected to improve graft integration prospects, as well as their long-term viability and strength. absence of supporting cells (24). The involvement of cell contractility in the formation of the vascular network was studied by inhibiting myosin II, a cytoskeletal protein responsible for force transmission within cells.…”
Section: Static Tensile Forces Influence Vascular Network Organizatiomentioning
confidence: 99%
“…[1][2][3][4] Several approaches are being investigated to achieve functional vascularization in engineered tissues similar to that seen in vivo. [4][5][6][7][8] However, less than optimal scaffold architecture remains as one of the crucial factors, which affect the depth, rate of vascular ingrowth, and spatial distribution of vessels in the engineered construct.…”
Section: Introductionmentioning
confidence: 99%
“…13 For functional vascularization of the construct, the role of material-driven properties such as compatibility, functionality, mechanical property, and degradation along with scaffold design parameters such as structure, porosity, pore size, and interconnectivity are important. 2,5,[14][15][16][17] The present work addresses this bioengineering problem at the interface of scaffold engineering and the biology of vascularization by offering a new and innovative solution.…”
Section: Introductionmentioning
confidence: 99%
“…An effective process to isolate acellular ECM from porcine myocardium tissue, was reported by us and was shown to maintain the mechanical and biochemical properties and the major ECM components as well as support the long-term survival of cardiomyocytes and mesenchymal stem cells (MSC) [7]. Moreover, thick acellular ECM patch derived from porcine left ventricle was shown to retain the major structure of its inherent vasculature [9] that can be used ex-or in vivo as conduits to feed the tissue bulk, thus overcome the diffusion barrier limiting survival of cells more than 100 μm away from the nearest blood vessel [10]. Yet, the re-endothelialization of these conduits remains a critical problem requiring optimized conditions to support the attachment, survival, and proliferation of endothelial cells, which might facilitate future functional angiogenesis upon transplantation.…”
Section: Introductionmentioning
confidence: 99%